Investigation of growth conditions, crystal structure and surface morphology of SmS films fabricated by MOCVD technique - Volodin, N.M.; Zavyalova, L.V.; Kirillov, A.I.; Svechnikov, S.V.; Prokopenko, I.V.; Khanova, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The polycrystalline SmS films were fabricated by MOCVD technique using a number of ditiocarbamates, synthesized by different techniques. The growth kinetics and temperature dependencies of the film growth rate are investigated, which allowed us to determine the activation energies and the reaction type. The investigations of the structure and surface morphology of films were carried out. The technological conditions are determined providing the fabrication of single-phase SmS films of cubic modification with the most ordered crystal structure.